Direitos do/da adolescente em risco na apuração de autoria de ato infracional na cidade de São Paulo - Moraes, Fabiana Vicente de (2020)
The central objective of this study is to know the presence of the right to social protection in the path taken by the adolescent, who responds to the process of verification of an infraction act in freedom, from the moment it is apprehended/captured in the act and placed under the custody of the State agents. The study deals with the examination of procedural acts that permeate the time gap between the seizure/ presentation to the police authority, drawing up of the writ of seizure, informal hearing by the Public Prosecutor's Office, judicial process of verification of the infraction act - until it receives the sentence of the Judge of the Court of Childhood and Youth. Court cases were examined, by sampling, recording the trajectory of 40 (forty) adolescents, from 12 to 18 years of age, between girls and boys, from the five Great Regions of the City of São Paulo, whose processes began in 2017 and 2018. These adolescentes, were kept at liberty together with those responsible, during the verification process, which took place under one of the six Special Courts for Children and Youth from the city of São Paulo. It is part of the conception that the adolescent is a developing "being" and holder of the right to “integral/social” protection as an inseparable attribute of his personality and, therefore, constitutes an inescapable, non-transferable and unavailable right, which must be assured, with absolute priority. The thesis is organized in three chapters. It builds on the political history of the rights of children and adolescents in Brazil and holds the debate on the concept of “integral/social” protection in addition to socio-educational action, guarantees due to the adolescent. The empirical study analyzes the extension of rights to the adolescent at risk in the determination of authorship of an infraction act. With strict observance of confidentiality and preservation of the identity of adolescents, the approximations revealed by the way official records were prepared, indicate that the absence of recognition of the adolescent as a social holder of rights, hinders the establishment of protection measures and verification of the social risks to which he and his family are exposed, in the trajectory of finding an infraction act in the city of São Paulo